If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(a-8)=18
We simplify the equation to the form, which is simple to understand
6(a-8)=18
Reorder the terms in parentheses
+(+6a-48)=18
Remove unnecessary parentheses
+6a-48=+18
We move all terms containing a to the left and all other terms to the right.
+6a=+18+48
We simplify left and right side of the equation.
+6a=+66
We divide both sides of the equation by 6 to get a.
a=11
| 5/9X6 | | 72x^2+7x-49=0 | | -6v^2+27v=12 | | 2(5x-4)-1=11 | | 5-6x-8=-15-4x | | -10=x+21 | | 4+(5*0.25)= | | 5x-x+10=0 | | 8x+10=6(8x) | | 3k+2k=2+6k | | (x*0.75)+(5*0.25)=4 | | -2x^2-3x+54=0 | | -2x-3x+54=0 | | -3+7k=1+8k | | Cos(x)+7x=0 | | 100x^2-x-10=0 | | 54=89-36y | | m+599.01=686.98 | | -12c^2-38c=-40 | | c-19.2=24.0 | | 11-8n=1-6n | | 7x+3x=77 | | a-108.8=-203.0 | | r^2+3-2=0 | | x^2+nx+3x+3n=0 | | 2x^2-3-5=0 | | m+19.32=23.86 | | x=3(13/12-4) | | 8x+2=7(x-3)+4 | | x^2-dx-cx+dc=0 | | -6+m=-3m+6m | | 2p-6=-12+8p |